2023
DOI: 10.33087/ekonomis.v7i2.1150
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Work-Life Balance and Workload on Job Satisfaction to Affect Nurse Performance

I Komang Oka Permadi,
I Komang Suryadnya Diputra,
Putu Ari Pertiwi Sanjiwani

Abstract: In the process of providing service, nurses are the most interactive healthcare personnel with patients. Nurses in public hospitals have a huge responsibility for providing quality health care. The study aims to confirm and re-test the impact of work-life balance and workload on job satisfaction and the performance of nurses. The sample determination uses the nonprobability sampling method with the technique of taking saturated samples (sensus), so that the entire population of 32 people is the sample. Path an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
0
0
2
Order By: Relevance
“…This can be interpreted as an expression of employees' willingness to fulfill assigned tasks and exceed their supervisors' expectations to the extent that WFI Satisfaction is perceived. Among the investigations that have addressed this effect, a notable study was conducted on a group of nurses by [39]. They found that Job Satisfaction achieved through WFI did not have a strong relationship with the nurses' performance, aligning with our study's findings.…”
Section: H3: Wfi Satisfaction Has a Positive Relationship With Wfi In...supporting
confidence: 87%
“…This can be interpreted as an expression of employees' willingness to fulfill assigned tasks and exceed their supervisors' expectations to the extent that WFI Satisfaction is perceived. Among the investigations that have addressed this effect, a notable study was conducted on a group of nurses by [39]. They found that Job Satisfaction achieved through WFI did not have a strong relationship with the nurses' performance, aligning with our study's findings.…”
Section: H3: Wfi Satisfaction Has a Positive Relationship With Wfi In...supporting
confidence: 87%
“…Selanjutnya, terkait dengan kinerja perawat, berbagai penelitian empiris terbaru menunjukkan adanya eratnya pengaruh Work-Life Balance atau keseimbangan kehidupan kerja dan kompensasi terhadap kinerja perawat (Permadi et al, 2023);Ratnawati, 2023;(Wayan Sri Pradnyani & Ganesha Rahyuda, 2022). Penelitian-penelitian terdahulu ini secara empiris membuktikan bahwa perawat cenderung memiliki kinerja yang tinggi jika unsur keseimbangan kehidupan kerja di tempatnya bekerja dapat terpenuhi dengan baik serta tercukupinya kompensasi yang diterimanya sebagai wujud dari penghargaan atas asuhan keperawatan yang dilakukannya.…”
Section: Pendahuluanunclassified
“…Work life balance pada dasarnya merupakan cara untuk karyawan dapat memiliki hidup yang sehat, sehingga hal tersebut memiliki pengaruh terhadap peningkatan kinerja perawat (Larasati et al, 2019). (Permadi et al, 2023) Selanjutnya, Kompensasi adalah semua pendapatan yang berbentuk uang, barang langsungatau tidak langsung yang diterima karyawan sebagai immbalan atas jasayang diberikan kepada perusahaan (Aprinawati et al, 2021). (Nugraha, A., & Tjahjawati, 2017) menyatakan bahwa konsep variabel kompensasi terdiri dari tiga dimensi diantaranya kompensasi finansial langsung, tidak langsung, dan non finansial.…”
Section: Pendahuluanunclassified